Focal segmental glomerulosclerosis in pediatric kidney transplantation: 30 years' experience. Issue 10 (October 2016) - Cleper, Roxana; Krause, Irit; Bar Nathan, Nathan; Mor, Maya; Dagan, Amit; Weissman, Irith; Frishberg, Yaakov; Rachamimov, Ruty; Mor, Eitan; Davidovits, Miriam
Abstract: From 1982 to 2011, 53 kidney transplantations (KT) for pediatric focal segmental glomerulosclerosis (FSGS) were recorded in the National Israeli Kidney Transplant Registry (NIKTR): 22—primary (1◦) FSGS, 25—proved/suspected genetic‐secondary (2◦) FSGS, six lost/incomplete files/other. Half (56%) of 23 patients with 2◦ FSGS were Israeli‐Arabs vs 29% of 1◦ FSGS KT recipients. 1◦ FSGS recurrence occurred in 64% (14/22) of 22 KT in 17 patients aged (median) 14 years vs 1/25 of 2◦ FSGS ( P <.001). Early graft days/nonfunction occurred in 9/14 (64%), 2/8 (25%) and 2/25 (4%) of recurrent 1◦ FSGS (rFSGS), nonr1◦ FSGS and 2◦ FSGS, respectively. Twelve biopsies performed in nine of these grafts at (median) 8 days (range 5–60 days) post‐KT showed: ATN‐5, suspected rejection‐4, rFSGS‐2, normal kidney‐1; rFSGS was diagnosed eventually in 8/9. Dialysis need during the first month post‐KT was significantly associated with FSGS recurrence: 6/14 (43%) for rFSGS vs 2/8 (25%) for non‐rFSGS. Plasmapheresis (PP) achieved complete and partial rFSGS remission in 5/9 and 2/9 grafts, respectively. Three grafts were excised during the first 60 days post‐KT for: nonfunction (1) and bleeding (2). Remaining grafts' GFR was: 78, 42, and 91 mL/min (median) at 5.3, 4.75, and 8 years follow‐up for non‐rFSGS, rFSGS, and 2◦ FSGS grafts, respectively. Conclusions: Early PP implementation should be considered after KT for 1◦ FSGS patients with early graft dysfunction despite delayed proteinuria and nonspecific biopsy.